Unraveling the regulatory network of barley grain metabolism through the integrative analysis of multiomics and mQTL - Ruilian Song; Yixiang Wang; Yanjun Li; Qifei Wang; Siyu Zhang; Dongfa Sun; Genlou Sun; Longqing Sun; Xifeng Ren (Nature Communications)
Abstract Although metabolites of barley grains have been analyzed, the changes in metabolite abundance and gene expression regulation mechanisms during barley grain development have not been elucidated. Here, we explore the dynamic accumulation patterns of metabolites in barley grains at six different developmental stages by analyzing high-resolution metabolomic and transcriptomic data from Huadamai6 and Huaai11. We detect 986 metabolites and 18,868 co-expressed genes. Meanwhile, we identify 1057 mQTLs associated with 553 metabolites in a double haploid (DH) population derived from these two cultivars, and integrate metabolome, transcriptome, and mQTL information to construct a global co-expression regulatory network of barley grain metabolism. Using this dataset, we excavate transcription factors and structural genes that regulate flavonoid metabolism pathway, and also reveal the complex mechanism of HvC1-1 and HvMYC-1 regulating grain color differentiation in the DH population. Our findings reveal the metabolic regulatory network of barley grains development, and provide valuable resources for future nutritional quality improvement and molecular design breeding of barley.